2020
DOI: 10.1186/s12964-020-00624-8
|View full text |Cite|
|
Sign up to set email alerts
|

Metabolic syndrome increases senescence-associated micro-RNAs in extracellular vesicles derived from swine and human mesenchymal stem/stromal cells

Abstract: Background The metabolic syndrome (MetS) is a combination of cardiovascular risk-factors, including obesity, hypertension, hyperglycemia, and insulin resistance. MetS may induce senescence in mesenchymal stem/stromal cells (MSC) and impact their micro-RNA (miRNA) content. We hypothesized that MetS also alters senescence-associated (SA) miRNAs in MSC-derived extracellular vesicles (EVs), and interferes with their function. Methods EVs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…Therefore, MetS-induced changes in the miRNA profile of EVs might have exerted important posttranscriptional changes in mitochondria-related genes in recipient cells, which might have contributed to mitochondrial injury and in turn, impaired the capacity of MetS-EVs to repair the stenotic kidney. Importantly, our findings are in agreement with our recent observation that MetS alters the miRNA cargo of human MSC-derived EVs [65], suggesting that MetSinduced changes in the content of EVs are conserved in human subjects. Therefore, miRNAs packed in MSCderived EVs may have important implications for the use of autologous EVs as a therapeutic regenerative strategy.…”
supporting
confidence: 93%
“…Therefore, MetS-induced changes in the miRNA profile of EVs might have exerted important posttranscriptional changes in mitochondria-related genes in recipient cells, which might have contributed to mitochondrial injury and in turn, impaired the capacity of MetS-EVs to repair the stenotic kidney. Importantly, our findings are in agreement with our recent observation that MetS alters the miRNA cargo of human MSC-derived EVs [65], suggesting that MetSinduced changes in the content of EVs are conserved in human subjects. Therefore, miRNAs packed in MSCderived EVs may have important implications for the use of autologous EVs as a therapeutic regenerative strategy.…”
supporting
confidence: 93%
“…The EV miRNA cargo in all samples was assessed by miRNA sequencing, as described ( Li et al, 2020 ; see Supplementary Material ), after passing quality control tests ( Supplementary Tables 1 , 2 ). Total RNA was extracted from EVs using the exoRNeasy Maxi Kit (cat#77044, Qiagen, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…At the same time, some researchers proposed that MSC-Exos can only partially relieve ageing kidney induced by renal artery stenosis [98]. MetS is able to change the amount of loading of miRNA on EVs, upregulate ageing-related miRNA in EVs, and even limit the use of EVs in exogenous regenerative therapy through abnormal transcription [99][100][101]. Zhao et al found that autologous ADMSCs can better preserve microcirculation through comparative studies, while ADMSC-EVs perform better in retaining intactness of nephrocytes and reducing necrosis [102].…”
Section: Msc-evs and Atherosclerotic Renovascular Diseasesmentioning
confidence: 99%